2021
DOI: 10.3389/fnbeh.2021.709392
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Linear Polyubiquitination Is a Critical Regulator of Contextual Fear Memory Formation

Abstract: Strong evidence supports that protein ubiquitination is a critical regulator of fear memory formation. However, as this work has focused on protein degradation, it is currently unknown whether polyubiquitin modifications that are independent of the proteasome are involved in learning-dependent synaptic plasticity. Here, we present the first evidence that atypical linear (M1) polyubiquitination, the only ubiquitin chain that does not occur at a lysine site and is largely independent of the proteasome, is critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Since our proteomic analysis examined only the 1 h time point, we defined proteins with increased abundance in our enriched samples as targets that are about to be degraded while those with decreased abundance were defined as having actively undergone degradation; confirmation for this assumption will be discussed below ( Figure 6 ). Importantly, we find that proteomic analyses on non-degradation polyubiquitin chains (M1) reveals few proteins with decreased abundance (Musaus et al, 2021 ), supporting that reduced levels in our K48 purified samples is likely indicative of the degradation process. Of the proteins with significantly altered levels, we identified 11 with increased abundance in K48-purified samples after fear learning, with 4 proteins found in females and 7 in males ( Figure 1C ), but no mutual proteins between the sexes.…”
Section: Resultssupporting
confidence: 84%
“…Since our proteomic analysis examined only the 1 h time point, we defined proteins with increased abundance in our enriched samples as targets that are about to be degraded while those with decreased abundance were defined as having actively undergone degradation; confirmation for this assumption will be discussed below ( Figure 6 ). Importantly, we find that proteomic analyses on non-degradation polyubiquitin chains (M1) reveals few proteins with decreased abundance (Musaus et al, 2021 ), supporting that reduced levels in our K48 purified samples is likely indicative of the degradation process. Of the proteins with significantly altered levels, we identified 11 with increased abundance in K48-purified samples after fear learning, with 4 proteins found in females and 7 in males ( Figure 1C ), but no mutual proteins between the sexes.…”
Section: Resultssupporting
confidence: 84%
“…PTMs such as acetylation and ubiquitylation were associated with functions in learning or memory abilities. 44,45 Except for the changed expression and activity of hippocampal proteins, marginal zinc deficiency after birth may change the PTMs of hippocampal proteins, and change the functions of proteins, and affect the learning and memory abilities of rats. Therefore, five common types of post-translational protein modifications of hippocampal proteins, including acetylation, 2-hydroxyisobutyrylation, crotonylation, succinylation and lysine malonylation, were carried out in order to investigate the effect of marginal zinc deficiency on the PTM.…”
Section: Papermentioning
confidence: 99%
“…It has been shown that while both sexes require protein degradation, they differ in their regulation of this process within the amygdala (Devulapalli et al, 2021;Devulapalli et al, 2019). In addition, it has been found that proteasome-independent linear polyubiquitination plays a critical role in synaptic plasticity and fear memory formation in the amygdala, though the protein targets of this ubiquitin modification varied by sex (Musaus et al, 2021). Male rats were found to have increased protein degradation in the amygdala following learning, while females had increased baseline levels of ubiquitin-proteasome activity and K48 polyubiquitin protein targeting (Devulapalli et al, 2021).…”
Section: The Ubiquitin-proteasome System and Its Role In Memory Forma...mentioning
confidence: 99%
“…Of note, we recently found that while both male and female rats need degradation-dependent and independent UPS signaling to regulate fear memory formation in the amygdala (Devulapalli et al, 2021;Musaus et al, 2021), they differ significantly in the protein targets of ubiquitin signaling following learning (Farrell et al, 2021). Furthermore, these sex differences in degradation-specific UPS extend into other brain regions involved in fear memory formation, including the hippocampus (Martin et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation